Sarah Cowper’s "Character" of John Locke - Goldie, Mark (Locke Studies, 2021)
Lady Sarah Cowper (1644-1720) is best known for her commonplace books, which preserve unique and variant versions of poems by Restoration “wits.” She also kept a diary, in which she recorded her readings and meditations. The diary contains an unnoticed encomiastic “Character” of John Locke, composed at his death. It is one of the earliest obituaries of him, but it was commonplaced from other sources. Her use of her sources exemplifies aspects of the manuscript circulation of texts and the ways in which the active selection and redaction of textual material reflected a reader’s own religious, political, and personal preoccupations. Cowper portrays Locke as a moral exemplar and Christian virtuoso, whose orthodoxy she defends, and whose latitudinarian and Whig commitments she shares.